2009
DOI: 10.1002/jcb.22255
|View full text |Cite
|
Sign up to set email alerts
|

SRrp37, a novel splicing regulator located in the nuclear speckles and nucleoli, interacts with SC35 and modulates alternative pre‐mRNA splicing in vivo

Abstract: We report here the identification and characterization of a novel SR-related protein, referred to as SRrp37, based on its apparent molecular weight and subcellular location. SRrp37 was identified through a yeast two-hybrid screen during the course of searching for proteins interacting with pNO40, a ribosomal 60S core subunit. SRrp37 exhibited two alternative spliced isoforms generated by differential usage of the translation start site with the longer one, SRrp37, initiating at first exon and the shorter, SRrp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…A previous study identified 59 proteins with polyS regions in the human genome; it is proposed that replicative slippage at the DNA level was most likely responsible for their facile evolution [8]. It is unclear if our proposed role for the polyS region of Jmjd6 applies to other polyS-containing proteins; however, SRrp37 possesses a polyS domain and has a dual localization in nuclear speckles and in the nucleolus [12]. This conclusion suggests that the function, and related structure, of the Jmjd6 polyS domain are probably also conserved.…”
Section: Discussionmentioning
confidence: 86%
“…A previous study identified 59 proteins with polyS regions in the human genome; it is proposed that replicative slippage at the DNA level was most likely responsible for their facile evolution [8]. It is unclear if our proposed role for the polyS region of Jmjd6 applies to other polyS-containing proteins; however, SRrp37 possesses a polyS domain and has a dual localization in nuclear speckles and in the nucleolus [12]. This conclusion suggests that the function, and related structure, of the Jmjd6 polyS domain are probably also conserved.…”
Section: Discussionmentioning
confidence: 86%
“…ZCCHC17 is a poorly understood protein that has been shown to interact with transcription factors (Chang et al, 2003;Joo et al, 2010) as well as splicing factors (Lin et al, 2017;Ouyang, 2009). ZCCHC17 contains a zinc-finger (CCHC) domain and a nuclear localization signal, and microscopy has localized ZCCHC17 to the nucleus and nucleolus (Chang et al, 2003;Gueydan et al, 2002;Lin et al, 2017;Ouyang, 2009). Although there is no published experimental study of ZCCHC17 protein in brain tissue, a recent metaanalysis of RNA expression data from six previous gene expression studies of AD brain tissue included ZCCHC17 as one of the top 30 most reliably downregulated genes in AD (Li et al, 2015).…”
Section: Zcchc17 Loss Correlates With Loss Of Synaptic Genes In Admentioning
confidence: 99%
“…155 This protein serves as a splicing regulator located in the nuclear speckles and nucleoli 155 and is predicted to be highly disordered. SRrp37 is involved in modulation of alternative pre-mRNA splicing with either 5' distal site activation or preferential use of 3' proximal site, and in case of infection by Herpes simplex virus (HSVI), this protein may act as a splicing inhibitor of HSVI pre-mRNA.…”
Section: Srrp37mentioning
confidence: 99%
“…SRrp37 is involved in modulation of alternative pre-mRNA splicing with either 5' distal site activation or preferential use of 3' proximal site, and in case of infection by Herpes simplex virus (HSVI), this protein may act as a splicing inhibitor of HSVI pre-mRNA. 155 The characteristic features of SRrp37 are high serine (13.5%) and arginine contents (12.8%) and the presence of 3 motifs, a serine-arginine (SR) dipeptide enriched region , a polyserine stretch (residues 258-282), and a potential nucleolar localization signal comprising a long array of basic amino acids (residues 286-312). 155 Scaffolding protein piccolo Piccolo is a 5065 residue-long scaffold protein, which is predicted to be highly disordered (it contains »85% disordered residues).…”
Section: Srrp37mentioning
confidence: 99%
See 1 more Smart Citation